Adaptive and Device Independent Planning Module for Task-Oriented Programming of Assembly Systems - Backhaus, J.; Reinhart, G. (Procedia CIRP, 2015)
The ability to enable a fast modification and system-change, in order to fulfil quickly changing market needs, is one of the essential requirements of future production systems. Two basic steps for an adaption of an automated production system to a new task are the reconfiguration and the reprogramming. Against this background, the central objective of this paper is the discussion of a new concept to simplify the application of task-oriented programming for assembly systems. Only abstract tasks are described in the task-oriented programming. The deduction of control code is done in a programming system. The advantages of task-oriented programming in means of time and complexity are often negated by the necessary effort to adapt a task-oriented programming system to the components and processes in a specific production system. Therefore, an adaptable task- oriented programming system that can be customized easily is the current research focus of the authors. The core of a task-oriented programming system is a planning module, in which the task description is transferred in code for the control of the system. Main subjects in the planning process are the separation in sub-steps as well as the identification of appropriate parameters and the chronological sequence of the sub-steps. Depending on the application (for example welding, gluing or pick and place operations) different algorithms and process knowledge are necessary. In this article a highly adaptable planning module based on a blackboard architecture and vendor independent device descriptions is discussed. The structural design of the planning module, its constituent parts and the description techniques for skills as well as products and processes are outlined. The advantages of the concept are illustrated by adapting the planning module for an industrial welding process.